An evaluation of the integration of standards and guidelines in community pharmacy practices - Hattingh, H. Laetitia; King, M.; Smith, N. (Springer, 2009)
Objective To explore the usefulness and implementation of practice standards in community pharmacy practice regarding contemporary core services. Setting Community pharmacies in South East Queensland, Australia. Method During August and September 2006 semi-structured interviews with community pharmacists explored practice processes and procedures and the utilisation of endorsed standards and guidelines. Thematic content analysis of the interviews, inductive analysis and continual comparison of categories and concepts enabled common and distinct themes to be clarified. Main outcome measure Usefulness and integration of practice standards in the provision of core pharmacy services, utilisation of support staff, record keeping and overall risk management processes in community pharmacy. Results Seventeen community pharmacists participated, representing a wide range of demographics, experience and pharmacy types. Staff utilisation and record keeping practices were analysed as well as two core services, namely: (1) the supply of over-the-counter medicines, and (2) the dispensing of prescriptions. The procedures followed concerning the supply of over-the-counter medicines varied. The majority of participants did not regard this as a pharmacist's immediate role, but rather relied on support staff to identify when the supply required a pharmacist's intervention. Whilst all participants involved dispensary assistants in the dispensing process, the delegation of procedures differed. Most participants did not clearly differentiate between pharmacists' and dispensary assistants' activities. Dispensing processes and the involvement of pharmacists in the provision of patient advice varied. Pharmacist intervention record keeping was uncommon and records of 'near misses' were not routinely kept by any of the participants. Conclusion A lack of integration of practice standards indicated a need to review the standards for relevance. Additionally, pharmacists need to re-evaluate workflow models and the delegation of tasks in the light of new roles and responsibilities. © 2009 Springer Science+Business Media B.V.